Evidence for the Use of Acellular Dermal Matrix in Implant-Based Breast Reconstruction - Gravina, Paula R.; Pettit, Rowland W.; Davis, Matthew J.; Winocour, Sebastian J.; Selber, Jesse C. (Seminars in Plastic Surgery, 2019)
Acellular dermal matrices (ADMs) are tissue grafts that have been specially processed to remove all cellular components. These machined biological scaffolds have become popular in a variety of surgical settings due to their rapid incorporation into living tissue. As ADMs are highly malleable and cause minimal inflammation, they have come to serve as a useful tool in implant-based breast reconstruction procedures. The major benefits of using an ADM in this setting include superior initial breast contouring, decreased risk of capsular contracture after implant insertion, and consistent sustained positioning of the reconstructed breast. Despite these advantages, these tissue grafts are foreign to the host, and postoperative complications following ADM insertion, including infection and seroma, have been well documented. When considering using ADMs in this setting, it is important to first consider patient-specific factors that could preclude their use, such as low body mass index, small breasts, or a history of radiation exposure to the breast tissue. ADM grafts are also expensive, which may present another barrier to their use. Review of the literature ultimately suggests a continued role for ADMs in implant-based breast reconstruction, and continued research in this field is warranted.
Keywords: acellular dermal matrix; breast reconstruction; implant-based reconstruction